Evaluation of short-term intraocular pressure changes after intravitreal injection of Conbercept in patients with diabetic macular edema - Hu, Yunyan; Zeng, Yunkao; Yang, Jing; Zeng, Xiaomin; Cao, Dan; Ou, Biqun; Zhang, Guanrong; Zhang, Liang (Frontiers in Pharmacology, 2022)
Background: The study concerning the influence of Conbercept, which is an anti-Vascular endothelial growth factor (VEGF) agent, in intraocular pressure (IOP) spike is limited and warrants further investigation. The current study aimed to investigate the changes of intraocular pressure after intravitreal injection (IVI) of Conbercept and evaluate the risk factors associated with intraocular pressure spikes. Methods: Patients with diabetic macular edema receiving intravitreal injection of 0.05 ml (0.5 mg) Conbercept were involved in the study. All patients underwent slit lamp examination to determine the status of phakia/pseudophakia. The axial length was measured using IOL Master 500 before intravitreal injection. Patients underwent a Conbercept intravitreal injection with a 30-gauge needle in a standard fashion. The intraocular pressure was measured 2 min before injection, and 2, 10, 30 min, 1, 2, 5, 24 h after injection using a rebound tonometer. The changes of intraocular pressure and the relevant risk factors were evaluated. Patients were subdivided into phakic group and pseudophakic group to analyze the effect of lens status on intraocular pressure changes. Results: Forty patients with a mean age of 62.48 ± 12.22 years were included in the study. The mean intraocular pressure values at baseline and 2, 10, 30 min, 1, 2, 5, 24 h after injection were 14.81 ± 3.13 mmHg, 26.80 ± 9.43 mmHg, 18.76 ± 6.16 mmHg, 16.54 ± 5.94 mmHg, 15.64 ± 3.75 mmHg, 14.46 ± 3.03 mmHg, 14.10 ± 1.88 mmHg, 14.23 ± 2.71 mmHg respectively. The intraocular pressure after injection for 2, 10 min was significantly higher than baseline (p < 0.001, p = 0.001, respectively). The intraocular pressure between baseline and post-injection for 30 min or beyond were comparable (all p > 0.05). No significant difference was found between the phakic group and pseudophakic group (p = 0.422). The changes of intraocular pressure were positively correlated with age (r = 0.329, p = 0.038), but negatively with axial length (r = −0.472, p = 0.002). Conclusion: intravitreal injection of Conbercept may cause rapid spike of intraocular pressure, but is safe with respect to short-term changes. The intraocular pressure in patients with older age and shorter axial length is more likely to be higher after intravitreal injection.